2016
DOI: 10.1016/j.conbuildmat.2016.06.063
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and mechanical properties of asphalt concrete containing conductive fibers and fillers

Abstract: Electrically conductive asphalt concrete has the potential to satisfy multifunctional applications. Designing such asphalt concrete needs to balance the electrical and mechanical performance of asphalt concrete. The objective of this study is to design electrically conductive asphalt concrete without compromising on the mechanical properties of asphalt concrete. In order to achieve this goal, various tests have been conducted to investigate the effects of electrically conductive additives (steel fiber and grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 20 publications
1
75
0
5
Order By: Relevance
“…It is worth noting that, all the weights presented in Table 2, were calculated with the aid of SG values provided in Table 1. According to literature, conductive fillers can be incorporated in asphalt-based materials by following either dry [7], [27], [28] or wet [29], [30] mixing method. In dry mixing method, all 19 the components including the conductive filler are mixed at a temperature range of 150-160°C 20 [7], [27], and in wet mixing method, the conductive fillers are first blended with bitumen at an 21 elevated temperature range of 170-180°C [29], [30], and then the modified bitumen is mixed 22 with other components.…”
Section: Specimen Fabricationmentioning
confidence: 99%
“…It is worth noting that, all the weights presented in Table 2, were calculated with the aid of SG values provided in Table 1. According to literature, conductive fillers can be incorporated in asphalt-based materials by following either dry [7], [27], [28] or wet [29], [30] mixing method. In dry mixing method, all 19 the components including the conductive filler are mixed at a temperature range of 150-160°C 20 [7], [27], and in wet mixing method, the conductive fillers are first blended with bitumen at an 21 elevated temperature range of 170-180°C [29], [30], and then the modified bitumen is mixed 22 with other components.…”
Section: Specimen Fabricationmentioning
confidence: 99%
“…This enhancement has led to the development of innovative asphalt pavements with advanced thermophysical properties and energyharvesting purposes, that are used for solar collection [9], snow melting [10], and crack-healing by external heating [11][12][13][14][15]. García et al [16] and Wang et al [17] demonstrated the effectiveness of metallic fibres over other conductive additives in asphalt mixtures, concluding that their morphology and flexibility favour electrical and thermal conductivity [18].…”
Section: Introductionmentioning
confidence: 99%
“…According to other studies [27][28][29][30], the electrical resistivity of the mixture slightly decreases with the additive content, until a critical value, called percolation threshold, where resistivity sharply decreases. The effect of adding slag or graphene on the electrical resistivity of the mixture is shown in Figure 12.…”
Section: Influence Of Slag and Graphene On The Electrical Resistivitymentioning
confidence: 90%
“…In the case of induction heating, electrical currents are induced by adding conductive particles in the composition of the mixture, and the heat is generated by the Joule effect [24][25][26]. Several additives and respective dosages were studied in order to maximize the conductivity of the mixture, such as steel wool, steel fibers, graphite, carbon black and carbon fibers [24,[27][28][29][30]. Another heating technique is microwave heating, that was found to be more effective than induction heating to heal cracks in asphalt roads [19].…”
Section: Introductionmentioning
confidence: 99%